Odpowiedzi

Najlepsza Odpowiedź!
2010-03-11T20:19:03+01:00
A)-7+3y+9+2y= 2+5y
b)x-3x+2-2x-7= -4x-5
c)-5x+4y-y-7x-9y= -12x-6y
d)4x+5-x-4+x-3x= x-1
e)0,5a-2a+9-0,5a-11,5= -2a-2,5
f)-14k+9k-13+k+3+4k= -10
g)-3k+2m+5m-7+k-m= -2k-7+6m
h)2x-4+3x-2= 5x-6
2010-03-11T20:20:46+01:00
A)2+5y
b)-4x-7
c)-12x-6y
d)1x+1
e)-2a-2,5
f) -10
g) -2k-7+6m
h) 5x-6
MAM NADZIEJĘ ŻE MOGŁAM POMÓC :)
2010-03-11T20:22:04+01:00
A)-7+3y+9+2y= -7+9+3y+2y= 2+5y
b)x-3x+2-2x-7= x-3x-2x+2-7= -4x-5
c)-5x+4y-y-7x-9y= -5x-7x+4y-y-9y= -12x-5y
d)4x+5-x-4+x-3x= 4x-x+x-3x+5-4= x+1
e)0,5a-2a+9-0,5a-11,5= 0,5a-2a-0,5a+9-11,5= -2a-2,5
f)-14k+9k-13+k+3+4k=-14k+9k+k+4k-13+3= k-10
g)-3k+2m+5m-7+k-m= -3k+k+2m+5m-m-7= -2k+6m-7
h)2x-4+3x-2= 2x+3x-4-2= 5x-6

to na tyle :)